A square antiprism dysprosium single-ion magnet with an energy barrier over 900 K. Issue 67 (1st August 2019) - Bala, Sukhen; Huang, Guo-Zhang; Ruan, Ze-Yu; Wu, Si-Guo; Liu, Yang; Wang, Long-Fei; Liu, Jun-Liang; Tong, Ming-Liang
Abstract : A stable and high-performance molecule displays a reversal barrier >900 K, which is the highest among square antiprismatic dysprosium single-ion magnets. Abstract : Herein we report a stable and high-performance Dy(iii ) single-ion magnet (SIM) showing an energy barrier of 944 K under zero dc field, with an open hysteresis loop up to 6 K. To the best of our knowledge, this is the highest energy barrier for a square antiprism as well as phosphine oxide based Dy-SIMs, reported so far.